Application of Economic Analysis of Law Theory as a Basis for Courts’ Judgements in Corruption Crime Cases: (Analyst’s Decision of 45/Pid.Sus/TPK/2011/PN.BDG) - Peter Jeremiah Setiawan; Madeleine Celandine Guinevere; Fauzy Iskandar Alamsyah; Mohammad Irvan (Musamus Law Review, 2021)
Mastery theory of law is one of the criteria for a good court. One of the law theories currently being developed is economic analysis of law theory. One of the decisions that the judge considered was using economic analysis of law theory in making a decision is a decision of 45/Pid.Sus/TPK/2011/PN.BDG. Therefore, this article will analyze further into the decision of 45/Pid.Sus/TPK/2011/PN.BDG. This research is legal research that uses statute approach, conceptual approach, and case approach. Based on the research, it showed that the features of economic analysis of law theory are: 1) Focused on the philosophy of justice utilitarianism which is the fundamental concept based on felicific calculus, 2) Using the basis of consideration: a) Economic theory as a foundation for legal analysis, b) Using analysis of cost-benefit to create a law and/or c) Consideration of opportunity cost which law will be formed, and 3) Output which is achieved is wealth maximization. Related to the Decision Number Register 45/Pid.Sus/TPK/2011/PN.BDG. in fact, arguable that judges make the decision based on economic analysis of law theory because related to ratio decedendi has fulfilled 3 (three) characteristic economic analysis of law theory.